2010
DOI: 10.1159/000306591
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Possible Stress-Related Biochemical Markers to Oxidative/Antioxidative Status in Obsessive-Compulsive Disorder

Abstract: Free radicals have been found to play an important role in obsessive-compulsive disorder (OCD). So, we measured the oxidative/antioxidative status of OCD patients, and assessed its use as a biological marker. The study was carried out on 20 healthy and 20 OCD subjects, aged between 20 and 40 years. Biochemical parameters of all subjects were assessed and compared. A significant difference in superoxide dismutase (SOD) levels was observed between the OCD and control groups (p < 0.05); malondialdehyde (MDA) leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
37
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(47 citation statements)
references
References 49 publications
7
37
0
Order By: Relevance
“…A causal link between these two was also very recently demonstrated by several authors [50][51][52][53][54]. Moreover, different cell types studied in anxious mice showed a strong accumulation of intracellular ROS, in comparison to non-anxious mice, suggesting that oxidative stress is present in various cortex areas, as well as in hippocampus and cerebellum [55,56].…”
Section: Discussionsupporting
confidence: 57%
“…A causal link between these two was also very recently demonstrated by several authors [50][51][52][53][54]. Moreover, different cell types studied in anxious mice showed a strong accumulation of intracellular ROS, in comparison to non-anxious mice, suggesting that oxidative stress is present in various cortex areas, as well as in hippocampus and cerebellum [55,56].…”
Section: Discussionsupporting
confidence: 57%
“…34 Cholesterol deficiency in neuronal membranes may also have a direct negative impact on synapse formation, dendritic outgrowth, and neuronal survival. 35 Moreover, as several studies have 36,37 shown that OCD patients may have increased oxidative stress and that this correlates with disease severity, we may speculate that lipid peroxidation might be one of the causes of reduced serum HDL-C and altered lipid profile in these patients. Alexithymia probably results from an inhibitory mechanism that could contribute to a suppression of emotional processing within the right hemisphere and to poorer verbalization of emotional contents (within the left hemisphere).…”
Section: Discussionmentioning
confidence: 89%
“…One such mechanism may involve oxidative stress, evidence of which has been described in OCD (Behl et al, 2010; Chakraborty et al, 2009; Selek et al, 2008). OCD is associated with polymorphisms of the neuronal glutamate transporter (EAAC1) gene, which mediates cysteine uptake necessary for neuronal glutathione (GSH) production (Aoyama et al, 2006; Monteiro and Feng, 2016).…”
Section: Insights Into Ocd From the Deer Mouse: A Platform For Resmentioning
confidence: 99%